Doctoral dissertation: Spatial Adjustments of Furniture Industry: a Comparison of Spain and Denmark (2006-2015) - Yingxin Wang (Boletín de la Asociación de Geógrafos Españoles)
Wang, Yingxin. Spatial Adjustments of Furniture Industry: a Comparison of Spain and Denmark (2006-2015). Autonomous University of Barcelona (Spain), july 2019. Directors: Montserrat Pallares-Barbera & Ana Vera. Retrieved from https://www.tdx.cat/handle/10803/667933#page=1